Speaking Assessments by Japanese English Teachers Pre and Post Implementation of CEFR in the Midst of a Global Pandemic - Ee, Emily Ching Choong; Pravina, Manoharan; Soubakeavathi, Rethinasamy (UPM Press, 2021)
Amid a global pandemic, while schools in many parts of the world were closed to adhere to quarantine orders, schools in Japan resumed face-to-face classes after only a month of closure with strict adherence to COVID-19 guidelines and standard operating procedures (SOP). This study examined how speaking assessments were administered face-to-face for Grade 5 and 6 elementary school students prior to and after introducing the Common European Framework of Reference (CEFR) and amid a global pandemic between April to October 2020. The paper also reports the challenges and strategies employed in carrying out the speaking assessments following the CEFR while adhering to the SOP. The study employed a qualitative research method that utilised semi-structured interviews to elicit information from four teachers who taught in eight schools within Niigata City, Japan. Findings suggest that prior to the implementation of CEFR, not all teachers carried out speaking assessments. However, the implementation of CEFR emphasised the need to teach speaking and carry out speaking assessments. The CEFR also served as guidance for the teachers in preparing the assessment scoring rubrics. The results also showed that the speaking assessments were implemented individually instead of in groups before the pandemic and the presence of the masks, which increased the student’s anxiety and affected their performance. However, the teachers employed various strategies to overcome the challenges by modifying the assessment tasks and utilising web conferencing technology.